2020
DOI: 10.1371/journal.ppat.1008795
|View full text |Cite
|
Sign up to set email alerts
|

An HSV-2 nucleoside-modified mRNA genital herpes vaccine containing glycoproteins gC, gD, and gE protects mice against HSV-1 genital lesions and latent infection

Abstract: HSV-1 causes 50% of first-time genital herpes infections in resource-rich countries and affects 190 million people worldwide. A prophylactic herpes vaccine is needed to protect against genital infections by both HSV-1 and HSV-2. Previously our laboratory developed a trivalent vaccine that targets glycoproteins C, D, and E present on the HSV-2 virion. We reported that this vaccine protects animals from genital disease and recurrent virus shedding following lethal HSV-2 challenge. Importantly the vaccine also ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
1
50
0
1
Order By: Relevance
“…As previous studies demonstrated the successful delivery of more than one HSV-2 glycoprotein to broaden antigen coverage via mRNA vaccination (31)(32)(33), we sought to determine if simultaneous immunization with mRNA-LNP expressing the chimeric spikes of diverse sarbecoviruses was a feasible strategy to elicit broadly binding and neutralizing antibodies. As aged human populations are the most susceptible to severe COVID-19 disease and death, we sought to examine the protective efficacy of our vaccines in aged mouse models that develop severe disease and death following sarbecovirus infection.…”
Section: Immunogenicity Of Mrnas Expressing Chimeric Spike Constructsmentioning
confidence: 99%
“…As previous studies demonstrated the successful delivery of more than one HSV-2 glycoprotein to broaden antigen coverage via mRNA vaccination (31)(32)(33), we sought to determine if simultaneous immunization with mRNA-LNP expressing the chimeric spikes of diverse sarbecoviruses was a feasible strategy to elicit broadly binding and neutralizing antibodies. As aged human populations are the most susceptible to severe COVID-19 disease and death, we sought to examine the protective efficacy of our vaccines in aged mouse models that develop severe disease and death following sarbecovirus infection.…”
Section: Immunogenicity Of Mrnas Expressing Chimeric Spike Constructsmentioning
confidence: 99%
“…The most common glycoprotein in these vaccines is gD. Other glycoproteins such as gB, gC, gE, gK were utilized in vaccines as well ( Corey et al., 1999 ; Stanfield et al., 2014 ; Awasthi et al., 2017 ; Egan et al., 2020 ). Unfortunately, some vaccines efficient in animal models failed in human clinical trials and were ceased recently.…”
Section: Viral Glycoproteins As Antiviral Targetsmentioning
confidence: 99%
“…Fortunately, some vaccines are continuing their clinical trials. The following vaccines are currently in clinical trials or show excellent results in preclinical trials: COR-1 ( Dutton et al., 2016 ; Chandra et al., 2019 ), NE-HSV2 ( Truong et al., 2019 ), HSV-2 trivalent vaccine ( Awasthi et al., 2014 ; Awasthi et al., 2017 ; Egan et al., 2020 ), G103 ( Odegard et al., 2016 ), HSV529 ( Bernard et al., 2015 ; Dropulic et al., 2017 ; Dropulic et al., 2019 ), RVX201 ( Halford et al., 2011 ), VC2, R2 ( Richards et al., 2017 ; Bernstein et al., 2020 ), HSV2 ΔgD2 ( Dropulic et al., 2017 ; Burn et al., 2018 ), and HSV-2 trivalent mRNA ( Egan et al., 2020 ). Hopefully, one or more of these may be developed into a successful vaccine to control HSV infection in the human population.…”
Section: Viral Glycoproteins As Antiviral Targetsmentioning
confidence: 99%
“…Data suggest that vaccines for HSV-6A and HSV-7 should also be high on the priority list [7]. Vaccines are already in development for HSV-1 and HSV-2 infections (review [35]).…”
Section: The Hypothesis and Its Explanation Of The Data On The Incidementioning
confidence: 99%